Modeling of diesel/CNG mixing in a pre-injection chamber - Abdul-Wahhab, H.A. (Institute of Physics Publishing, 2015)
Diesel engines performance can be improved by adding combustible gases to the liquid diesel. In this paper, the propagation of a two phase flow liquid-gas fuel mixture into a pre-mixer is investigated numerically by computational fluid dynamics simulation. CNG was injected into the diesel within a cylindrical conduit operates as pre-mixer. Four injection models of Diesel-CNG were simulated using ANSYS-FLUENT commercial software. Two CNG jet diameters were used of 1 and 2 mm and the diesel pipe diameter was 9 mm. Two configurations were considered for the gas injection. In the first the gas was injected from one side while for the second two side entries were used. The CNG to Diesel pressure ratio was varied between 1.5 and 3. The CNG to Diesel mass flow ratios were varied between 0.7 and 0.9. The results demonstrate that using double-sided injection increased the homogeneity of the mixture due to the swirl and acceleration of the mixture. Mass fraction, in both cases, was found to increase as the mixture flows towards the exit. As a result, this enhanced mixing is likely to lead to improvement in the combustion performance.